Local knowledge and global concerns: artificial glaciers as a focus of environmental knowledge and development interventions - Nüsser, Marcus; Baghel, Ravi (Ethnic and Cultural Dimensions of Knowledge, 2016)
In recent years Himalayan glaciers have figured controversially in the public discussion of climate change, reflecting the tension between the mounting global concern over these ostensibly threatened cryoscapes and the dominant local role that glaciers play in irrigation. The intersection of local and global knowledge of the Himalayas is evident in the construction of artificial glaciers in Ladakh, a high altitude desert in the geopolitically sensitive region of Kashmir, bordering India, Pakistan, and China. These artificial glaciers meet local irrigation needs in the agricultural season by melting before natural glacial meltwater becomes available. At the same time, these ice reservoirs are also framed as an adaptation to climate change, a perspective suggesting that, contrary to romanticized notions, local knowledge is neither purely local nor disconnected from globally circulating knowledge about climate change.